Interpretação da crise financeira mundial sob a perspectiva de David Harvey - Martinez, Felipe Pasini Paez [UNESP] (2014)
The world economy experiences a recession, where there are low dynamism and insignificant growth of productive activity. This scenario comes from the global financial crisis of 2008, as a result of the international financial system configuration, and spread systemically to the real side of the global economy. In addition to its specificities, and with the exception of its scope and severity, this economic crisis is not different from past crises that hit the globe over the past thirty years. Resulting from fusion of two highly speculative capital, financial capital and real estate capital, this crisis originated in the incessant struggle of capital to seek alternative for its appreciation given the limitations inherent in their nature, in other words, to try to avoid capital depreciation periods (crisis), alternative mechanisms arise that stretch and delay this fate, but at the same time act to raise the severity and complexity of these crises. Therefore, the aim of this work is to interpret the current economic crisis through the perspective of marxist David Harvey and his theory, trying to clarify and identify its origin and its implications for the current economic order and the current pattern of development